PEMASANGAN SISTEM DISTRIBUSI PADA JARINGAN TEGANGAN RENDAH DI PLN ULP BREBES - Ahmad Hanif Shafwan; Rahmat Hidayat (Jurnal Ilmiah Wahana Pendidikan, 2023)
The existence of electricity which has reached various environments makes its presence inseparable in all community activities such as households, businesses and industry. On the other hand, there are frequent disturbances related to technical and non-technical overload factors. 2 Household and commercial consumers are usually connected to the secondary distribution network through the electric house connection. Consumers who require higher voltages can apply to be directly connected to the primary distribution network, or to the subtransmission level. In this regard, this study aims to analyze and document the installation of systems on low voltage networks at PLN ULP Brebes. The methods used include field surveys, interviews, and historical collection and analysis related to the installation of distribution systems in the area. The results showed that the installation of the distribution system on the low voltage network at PLN ULP Brebes was carried out with various technical and reliability considerations. The planning phase involves analyzing power requirements, selecting cable types, and selecting network locations. The design of the distribution system is carried out by considering efficiency, reliability and the ability to cope with load spikes. The installation process involves installing poles, cables and other equipment following established safety standards and procedures. In addition, tests and tests are carried out to ensure that the distribution system is functioning properly and conforms to the set quality standards. The documentation resulting from this research provides a useful guide for PLN ULP Brebes in installing distribution systems on low voltage networks. This can help improve the reliability, efficiency and quality of the electrical service provided to customers.